The effect of basic medical insurance on the changes of primary care seeking behavior: An application of hierarchical age-period-cohort analysis - Cao, Na; Li, Xuyang; Jiang, Junfeng; Xu, Wenyan (Frontiers in Public Health, 2022)
Abstract In order to encourage residents to go to primary care facilities, China has set up differentiated basic medical insurance reimbursement ratios. The study aims to use the dynamic point of view of longitudinal data to examine the changes in the impact of basic medical insurance on primary care. The data for this study comes from the Chinese Family Panel Research(CFPS) in 2010, 2012, 2014, 2016 and 2018. We adopted Hierarchal Age-period-cohort-Cross-Classified Random Effects Models (HAPC-CCREM) to examine the changes in the impact of basic medical insurance on primary care. Compared with non-insured groups, participants of New Rural Cooperative Medical System (coefficient=0.730) have a relatively high incidence of primary care seeks, while Urban Residents’ Basic Medical Insurance (coefficient=-0.482) and Urban Employees’ Basic Medical Insurance (coefficient=-0.663) are lower, respectively. However, age and period over time have a more obvious moderating effect on primary care seeks. The increase of age makes the participation of URBMI and UEBMI to increase the negative impact on primary care seeks. As for NRCMS, its effect on the probability of consultation at the primary level shows a trend of increasing first and then decreasing. The study of primary care behavior is an important direction for the construction of a hierarchical medical system. As basic medical insurance is the source of power for the hierarchical medical system, we can provide certain direction for policy formulation on the changes of basic medical insurance in primary care behavior.